Pengaruh Bahan Bantu Terhadap Volume Produksi Logam Timah di PT. Timah Tbk Muntok, Bangka Barat - Frans Dito; Sulida Erliyana; Karjono (Politeknik bumi Akpelni, 2025)
This study aims to analyze the effect of auxiliary materials on the production volume of tin metal at PT Timah Tbk, Muntok, West Bangka. A descriptive quantitative approach was employed, presenting data in numerical form to assess the degree of influence between the examined variables. The sampling technique followed the minimum requirement of 20 times the number of variables. With two variables under investigation, a total of 40 samples were collected. Data analysis was conducted using simple linear regression to determine the significance of the relationship between auxiliary materials and production volume. The results indicate a positive and significant effect of auxiliary materials on tin metal production volume. This is evidenced by a significance value (Sig.) of 0.000, which is lower than the alpha level of 0.05, and a t-value of 5.484, which exceeds the t-table value of 2.024. Consequently, the null hypothesis (H₀) is rejected, and the alternative hypothesis (Hₐ) is accepted. These findings confirm that the availability and application of auxiliary materials play a crucial role in enhancing the production volume of tin metal within the company.